Comparați numerele: a=(3-√7)*√16+√7
b=(4+2√3)(√3-1)²
Răspunsuri la întrebare
Răspuns de
0
a = (3-√7)*√16+√7 = (3-√7)*4+√7 = 12-4√7+√7 = 12-3√7=3(4-√7)
b = (4+2√3)(√3-1)² = (4+2√3)(√3²-2√3+1²) = (4+2√3)(3-2√3+1) =
(4+2√3)(4-2√3) = 4²-(2√3)² = 16-12 = 4
=>
3(4-√7) şi 4 => √9(√16-√7) şi √16 =>
a > b
b = (4+2√3)(√3-1)² = (4+2√3)(√3²-2√3+1²) = (4+2√3)(3-2√3+1) =
(4+2√3)(4-2√3) = 4²-(2√3)² = 16-12 = 4
=>
3(4-√7) şi 4 => √9(√16-√7) şi √16 =>
a > b
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Engleza,
9 ani în urmă
Fizică,
9 ani în urmă
Limba română,
9 ani în urmă